ROLE OF PROLINE ACID IN IMPROVING SUNFLOWER YIELD AND YIELD COMPONENTS UNDER DEFICIT CONDITIONS WATER - & Alag, Abass (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field study was conducted during the spring and autumn seasons of 2014 at the experimental farm of Field Crop Department, College of  Agriculture (Abo-Ghraib) - University of Baghdad, to study the effect of Irrigation deficiency quantities and concentrations of Proline acid on yield , its components, water consumptive and water use efficiency of sunflower (Helianthus annus L. ) for Luleo hybrid. Randomized Complete Block Design (RCBD) in arrangement of a split-plot with three replications were used. Irrigation treatments, control (depletion  50% of available water) and 60% , 50%  40% of control treatment, were assigned as a main plots. while proline acid concentrations of 0, 30, 60 and 90 mg.L-1 were assigned as a subplots. The results showed that there is no significant differences between the control treatment and 60% of the control for  the period from planting to 50% flowering, number of leaves, relative water content, nitrogen concentration in leaves, fertilization percentage, number of seeds in the head,100 seed weight and seeds yield reaching 3.90, 2.46 t.ha-1  and 3.78 , 2.41 t.ha-1 for spring and autumn seasons respectively. which indicates the possibility of saving 40% of the water consumption which is estimated 1920.00, 2960.00 m3. ha-1. Season-1  for two seasons respectively without any yield reduction. While the percentage of decline in seeds yield for treatments 50% and 40% from the control treatment for spring season were 14.61%  , 19.74% respectively and 21.95 % , 33.33% for autumn season comparing with control. Irrigation treatment 40%, 60% of the control treatments gave the best water use efficiency for both seasons respectively. a concentrations of Proline acid affect significantly most of studied traits. Increasing of Proline to 60mg.L-1 gave the to increase in fertilization percentage was  و70.2081.% 100 seed weight7.12 و7.52 gm, seed yield 3.75, 2.21 t.ha-1 and water use efficiency 0.84 و0.29  kg seed.m-3 water comparing with control for two seasons respectively .The interaction between irrigation and Proline acid showed a significantly effect on all characteristics seeds yield components traits in both seasons. We therefore recommend that in case of limited  irrigation water  by %60 by the need of the full irrigation (50 % depletion of available water) without a significant decrease in product seed yield, in addition to possibility treatment of  sunflower plants with Proline acid with 60 mg .L-1 to improvement capacity of water stress.